2013
DOI: 10.1109/tcpmt.2013.2245377
|View full text |Cite
|
Sign up to set email alerts
|

Macromodeling of Multilayered Power Distribution Networks Based on Multiconductor Transmission Line Approach

Abstract: Typical modeling algorithms for multilayered irregular shaped power distribution networks are based on a finite difference solution of the Helmholtz equation. In this paper, the finite difference solution is demonstrated to be equivalent to a discretization of the Telegraphers partial differential equations for multiconductor transmission lines (MTL). With this concept, an efficient macromodeling algorithm for multilayered structures based on MTL theory is presented. The electromagnetic coupling between the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We found that the addition of fringing capacitances at the edges was not necessary for the models tested. Stamping all the elements into the MNA matrix results in (9). This allows the computation of all the desired quantities like the impedances of interest.…”
Section: A Inductance Model For Plane-pair Peec (Ppp)mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the addition of fringing capacitances at the edges was not necessary for the models tested. Stamping all the elements into the MNA matrix results in (9). This allows the computation of all the desired quantities like the impedances of interest.…”
Section: A Inductance Model For Plane-pair Peec (Ppp)mentioning
confidence: 99%
“…There are several different formulations used for modeling the plane-pairs. Some are based on analytical formulations like [5], [6], finite difference time domain (FDTD) models like [7], transmission line modeling (TLM) approach like [8], [9], etc. The first partial element equivalent circuit (PEEC) [10] based approach in plane-pair modeling was presented in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Powerful ultra-wideband (UWB) pulses of the nanosecond and sub-nanosecond ranges can penetrate and damage various radioelectronic devices (REDs). Engineers consider conducted interference, induced interference in a system, and radiated interference between systems [1]. To ensure electromagnetic compatibility (EMC) of electronic systems, an electromagnetic interference must be controlled and limited.…”
Section: Introductionmentioning
confidence: 99%
“…Powerful ultra-wideband (UWB) pulses of the nanosecond and sub-nanosecond ranges can penetrate and damage various radioelectronic devices (REDs). Engineers consider conducted interference, induced interference in a system, and radiated interference between systems [1]. To ensure electromagnetic compatibility (EMC) of electronic systems, an electromagnetic interference must be controlled and limited.…”
Section: Introductionmentioning
confidence: 99%